2016
DOI: 10.7860/jcdr/2016/18303.7395
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Changes in Electroacupuncture Treated Polycystic Ovary in Rats

Abstract: IntRoductIonCardiovascular disease (CVD) in one of the most common metabolic disorder in women with polycystic ovary syndrome, it is also associated with insulin resistance, hyperandrogenism and obesity [1,2]. Young women with PCOS have increased sympathetic and decreased parasympathetic activity in heart measured by heart rate variability (HRV) [3].Autonomic imbalance in heart is related to CVD, group of women with PCOS has high risk of CVD [4]. Heart rate fluctuation is an indication of autonomic nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Previous clinical research showed that AEA resulted in improvement in HRV LF/HF ratios over the course of the protocol intervention, implying improved sympathovagal balance [44]; however, this was measured using ambulatory HRV monitoring, which has not been validated against the gold standard of electrocardiogram (ECG) recordings. To date, the effect of acupuncture on HRV in women with PCOS has not been evaluated, although electro-acupuncture improved HRV and restored oestrous cycling compared to sham handling in a recent rat study [73].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical research showed that AEA resulted in improvement in HRV LF/HF ratios over the course of the protocol intervention, implying improved sympathovagal balance [44]; however, this was measured using ambulatory HRV monitoring, which has not been validated against the gold standard of electrocardiogram (ECG) recordings. To date, the effect of acupuncture on HRV in women with PCOS has not been evaluated, although electro-acupuncture improved HRV and restored oestrous cycling compared to sham handling in a recent rat study [73].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study by Johnson et al (2011), LF was higher than HF spectral power, which would indicate the predominance of baroreceptor activity. In a study by Ramadoss et al (2016), the values of frequency parameters were significantly higher compared to other studies and, therefore, were not included in the average values presented in Table 1, and the LF/HF ratio indicates the balance between the sympathetic and parasympathetic systems. VLF spectral power has not been evaluated.…”
Section: Hr Variability In Conscious Female Ratsmentioning
confidence: 95%
“…Although hypotheses regarding sex differences in the activities of the ANS measured according HRV have not yet been confirmed, they have not been rejected because there are only four studies that involved conscious female rats (Johnson et al, 2011;Koresh et al, 2016;Ramadoss et al, 2016;Singh et al, 2018) whereas the control values from individual studies are not unequivocal. For example, in a study by Johnson et al (2011), LF was higher than HF spectral power, which would indicate the predominance of baroreceptor activity.…”
Section: Hr Variability In Conscious Female Ratsmentioning
confidence: 99%
“…Therefore, in our laboratory, we aimed to investigate the autonomic alteration of the HR in women with PCOS and the effect of EAT on it. For this study, we used the estradiol valerate (EV)-induced PCO rat model [47]. In this study, the vaginal smear was taken periodically from the control and experimental group rats.…”
Section: Eat Rectifies the Autonomic Alteration In Women With Pcos 10...mentioning
confidence: 99%